The searchers [videorecording (DVD)] - Wayne, John, 1907-1979; Hunter, Jeffrey, 1926-1969; Miles, Vera; Bond, Ward, 1903-1960; Wood, Natalie; Qualen, John, 1899-1987; Carey, Olive; Brandon, Henry, 1912-1990; Curtis, Ken, 1916-1991; Carey, Harry, Jr., 1921-2012; Moreno, Antonio, 1887-1967; Worden, Hank, 1901-1992; et al. (John Wayne collection., 2007)
A Civil War veteran spends five years on the trail of a Comanche raiding party that kidnapped his dead brother's daughters. Breathtaking scenery gives a picture of frontier families separated by miles of emptiness.